2021
DOI: 10.3390/fluids6030108
|View full text |Cite
|
Sign up to set email alerts
|

Vibroconvective Patterns in a Layer under Translational Vibrations of Circular Polarization

Abstract: This article experimentally investigates thermal vibrational convection in horizontal layers, subject to circular translational oscillations in the horizontal plane. The definite direction of translational vibrations lacks investigation, and the case of a layer heated from above is considered. At large negative values of the gravitational Rayleigh number, the thermovibrational convection appears in a threshold manner with an increase in the vibration intensity. Our results show that in the case of strong gravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Begin the study of vibrational thermal convection generated by a rotating force field in a cavity that performs independent rotation with the limiting case of no rotation. The researches of the problem in this statement was started in (Kozlov et al 2021). The visualization technique with using thermochromic film described above makes it possible to display weak changes in liquid temperature near the lower "cold" boundary of the cavity.…”
Section: Thermal Vibrational Convection Without Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Begin the study of vibrational thermal convection generated by a rotating force field in a cavity that performs independent rotation with the limiting case of no rotation. The researches of the problem in this statement was started in (Kozlov et al 2021). The visualization technique with using thermochromic film described above makes it possible to display weak changes in liquid temperature near the lower "cold" boundary of the cavity.…”
Section: Thermal Vibrational Convection Without Rotationmentioning
confidence: 99%
“…Thermal vibrational convection under the action of circularly polarized translational vibrations was theoretically considered in (Kozlov 1991, Pesch et al 2008, in this case, the uniform inertial force field rotates in the reference frame of the cavity. An experimental study of thermovibrational convection in a plane horizontal liquid layer heated from above was carried out in (Kozlov et al 2019, Kozlov et al 2021. Under conditions of large negative values of the gravitational Rayleigh number, it was found that vibrational convection develops in the form of spatial structures, where the elongated convective rolls are broken along the length into relatively short segments forming a beads-like pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Following the treatment of thermogravitational and thermocapillary convection, two studies [8,9] are also included, which concentrate on a third fundamental variant of thermally induced flows, namely fluid motion produced in non-isothermal systems by the application of "vibrations" (thermovibrational convection). Vibrations enable a timevarying acceleration, which formally makes the emerging convective structures a variant of buoyancy convection.…”
mentioning
confidence: 99%
“…The need to overcome a threshold to induce convection from an initial quiescent state, together with the opposite tendency of acceleration to damp fluid motion when its sign is reversed, causes a variety of possible solutions that can display synchronous, non-synchronous, time-periodic and multi-frequency responses. A very special case is represented by "circular translational vibrations", i.e., a situation where the entire fluid domain moves along a circular path [9]. The peculiarity of this flow originates from the absence of a preferred direction for the vibrations and the existence of a rotating force field in the non-inertial reference frame moving with the fluid container.…”
mentioning
confidence: 99%
See 1 more Smart Citation